Non-violent resistance parental training versus treatment as usual for children and adolescents with severe tyrannical behavior: a randomized controlled trial - Fongaro, Erica; Aouinti, Safa; Picot, Marie-Christine; Pupier, Florence; Omer, Haim; Franc, Nathalie; Purper-Ouakil, Diane (Frontiers in Psychiatry, 2023)
Objective: This single-blinded, randomized, parallel group superiority trial evaluates whether the Non-Violent Resistance (NVR) program, a 10-session parental-group intervention, was more effective in reducing stress in parents of children aged 6-20 years and displaying severe tyrannical behaviour (STB) compared to a treatment as usual (TAU) intervention that provided supportive counseling and psychoeducation. Methods: 82 parents of youth aged 6-20 years with STB were enrolled by the Child and Adolescent Psychiatry Department at the University Hospital of Montpellier (France). A random block and stratified by age (6-12 and 13-20 years) randomization, was performed. All participants were interviewed by independent, blinded to group assignments, research assistants, and completed their assessments at baseline and treatment completion (4 months from baseline). Since this program has not been previously evaluated in this population, the study primarily evaluated the efficacy, using the Parenting Stress Index/Short Form (PSI-SF). The primary outcome was the change from baseline to treatment completion of the PSI-SF total score. Results: 73 participants completed the study and were available for analysis (36 NVR and 37 TAU). At completion, between-groups comparison of the change (completion minus baseline) in the total score of PSI-SF was not significant (NVR: -4.3 (± 13.9); TAU: -7.6 (± 19.6); two-sample t-test p = .43); effect size of -0.19 [-0.67, 0.28]). Conclusions: Contrary to our expectation, NVR was not superior to TAU in reducing parental stress at completion for parents of children with STB. However, NVR showed positive outcomes in the follow-up, pointing to the importance to implement parental strategies and following this population over longer time periods in future projects.